Higher Ventricular-Arterial Coupling Derived from Three-Dimensional Echocardiography Is Associated with a Worse Clinical Outcome in Systemic Sclerosis - Francesco Tona; Elisabetta Zanatta; Roberta Montisci; Denisa Muraru; Elena Beccegato; Elena De Zorzi; Francesco Benvenuti; Giovanni Civieri; Franco Cozzi; Sabino Iliceto; Andrea Doria (Pharmaceuticals, 2021)
Primary myocardial involvement is common in systemic sclerosis (SSc). Ventricular-arterial coupling (VAC) reflecting the interplay between ventricular performance and arterial load, is a key determinant of cardiovascular (CV) performance. We aimed to investigate VAC, VAC-derived indices, and the potential association between altered VAC and survival free from death/hospitalization for major adverse CV events (MACE) in scleroderma. Only SSc patients without any anamnestic and echocardiographic evidence of primary myocardial involvement who underwent three-dimensional echocardiography (3DE) were included in this cross-sectional study and compared with healthy matched controls. 3DE was used for noninvasive measurements of end-systolic elastance (Ees), arterial elastance (Ea), VAC (Ea/Ees) and end-diastolic elastance (Eed); the occurrence of death/hospitalization for MACE was recorded during follow-up. Sixty-five SSc patients (54 female; aged 56 ± 14 years) were included. Ees (p = 0.04), Ea (p = 0.04) and Eed (p = 0.01) were higher in patients vs. controls. Thus, VAC was similar in both groups. Ees was lower and VAC was higher in patients with diffuse cutaneous form (dcSSc) vs. patients with limited form (lcSSc) (p = 0.001 and p = 0.02, respectively). Over a median follow-up of 4 years, four patients died for heart failure and 34 were hospitalized for CV events. In patients with VAC > 0.63 the risk of MACE was higher (HR 2.5; 95% CI 1.13–5.7; p = 0.01) and survival free from death/hospitalization was lower (p = 0.005) than in those with VAC < 0.63. Our study suggests that VAC may be impaired in SSc patients without signs and symptoms of primary myocardial involvement. Moreover, VAC appears to have a prognostic role in SSc.